Competitive Careers as a Way to Mediocracy - Matthias Kräkel (University of Bonn, Bonn Graduate School of Economics (BGSE), 2009)
We show that in competitive careers based on individual performance the least productive individuals may have the highest probabilities to be promoted to top positions. These individuals have the lowest fall-back positions and, hence, the highest incentives to succeed in career contests. This detrimental incentive effect exists irrespective of whether effort and talent are substitutes or complements in the underlying contest-success function. However, in case of complements the incentive effect may be be outweighed by a productivity effect that favors high effort choices by the more talented individual
Keywords: D72; J44; J45; M51; 330; career competition; contest; mediocracy; Erwerbsverlauf; Wettbewerb; Extensives Spiel; Leistungsmotivation; Arbeitsproduktivität; Leistungsorientierte Vergütung; Theorie